Phytotoxic Activity Analysis of 2-Methoxyphenol and 2,6-Di-tert-butyl-4-methylphenol Present in Cistus ladanifer L. Essential Oil - Diego Orellana Dávila; David F. Frazão; Amélia M. Silva; Teresa Sosa Díaz (Plants)
The evaluation of the wide variety of allelochemicals present in allelopathic plants allows the detection of safer bioherbicides with new mechanisms of action. This study tested two phenolic compounds of Cistus ladanifer essential oil (2-Methoxyphenol and 2,6-Di-tert-butyl-4-methylphenol), which are commercially available. At 0.01 mM, these compounds, both separately and in combination (1/1), inhibited up to over 50% of germination, cotyledon emergence and seedling growth of Lactuca sativa for the tests conducted on paper. Against Allium cepa, cotyledon emergence and seedling growth were inhibited at 0.5 mM. When the tests were carried out in the soil, the mixture of the two study compounds significantly inhibited the germination of L. sativa and A. cepa when applied at 0.5 and 1 mM, respectively, and seedling growth inhibition was greater for the latter in the paper tests. The greatest inhibitions were observed, with the highest concentrations analysed. Although there was no statistically significant difference among treatments, 2-Methoxyphenol seemed to affect germination and cotyledon emergence to a greater extent, whereas 2,6-Di-tert-butyl-4-methylphenol had a greater impact on seedling size. The effect of the mixture was greater than that of both compounds separately.